The Role of Design And Decoration in Enriching Children’s Clothes (Journal of the College of Education for Women, 2019)
As the child is growing up, he goes through different phases which will be accompanied by physical and psychological changes. These changes set the basis for processes of designing and making children's clothes which in turn give its required benefits and meet the physiological, psychological and community needs. That will help provide the child with healthy physical and psychological growth.The aim of this research is to recognize the decoration of clothes by colors and drawings and its role in clothes' richness and children's education. The research limits are objective, The limits are for female (3-5) years old. The research was done in teaching kindergarten in the college of education for women in 2016. The researchers found many conclusions , recommendations and suggestions . One of the best results found was regarding color (The red color got high percentage towards 3 years old girls) because it attracts the child and sensible to him. Regarding the designing , the looseness style with gentle and simple decoration got the highest percentage.Depending on that results , the researchers go out with some recommendations.